Isotope characterisation of deep aquifers in the Gwda catchment, northern Poland - Kotowski, Tomasz; Satora, Stefan (Geologos, 2016)
We present the results of isotope measurements (δ18O, δ D, δ13CDIC and 14C) and chemical analyses (TDS, TOC, HCO3-, SO42-, Cl-, NO3-, NH4+, Ca2+, Mg2+ Na+ and K+) conducted on groundwater samples collected from deep Cenozoic aquifers. These aquifers are the basic source of drinking water at numerous localities within the study area in northern Poland. Most of the δ18O determinations are characterised by low variability (i.e., > 70 per cent of δ18O are between -9.5‰ and -9.2‰). In most cases tritium activity was not detected or its content slightly exceeded the uncertainty of measurement (from ±0.3 T.U. to ± 0.5 T.U.). On average, 14C activity is twice higher than that under similar conditions and in hydrogeological systems. The δ13CDIC values fall within the -13.6‰ to -12.8‰ range. A slight variability is observed when considering all isotope and chemical data within the study area and under these hydrogeological conditions. In general, the results of isotope and chemical analyses seem to be homogeneous, indicating the presence of closely similar groundwaters in the system, irrespective of geological formation. It is likely that there is a significant hydraulic connection between shallow and deep aquifers in the Gwda catchment, which indicates the potential for seepage of pollutants from shallow Pleistocene to deep Miocene aquifers. This can endanger the latter by e.g., high concentrations of NO3-, SO42- and Cl- ions from shallow aquifers within the Gwda catchment.